Depression is a major determinant of both disease-specific and generic health-related quality of life in people with severe COPD. (14th November 2018) - Jang, Sun Mi; Kim, Ki Uk; Na, Hae Jung; Song, Seung Eun; Lee, Sang Hee; Lee, Haejung; Kim, Yun Seong; Lee, Min Ki; Park, Hye-Kyung
The quality of life of patients with chronic obstructive pulmonary disease (COPD) decreases significantly as the disease progresses; those with severe COPD are affected most. This article investigates predictors of the disease-specific and generic health-related quality of life (HRQL) in patients with severe COPD. This multicentre prospective cross-sectional study enrolled 80 patients with severe COPD. At enrolment, all patients completed a disease-specific instrument, the St George's Respiratory Questionnaire (SGRQ), and a generic instrument, the Short Form 36 Health Survey Questionnaire (SF-36). The data were analyzed by Pearson's correlation and multiple linear regression. The mean age of the patients was 66 ± 8 years; 93% were males. The SGRQ and SF-36 scores were not influenced by age or sex. Depression, dyspnea, the number of exacerbations, and exercise capacity significantly predicted the total SGRQ score ( p < 0.05). Depression was the strongest determinant of the total SGRQ score. The SF-36 physical component summary scores were related to depression, dyspnea, and the number of exacerbations ( p < 0.05). In comparison, the SF-36 mental component summary scores were related to depression and anxiety ( p < 0.05). Depression is a significant determinant of both the disease-specific and generic HRQL in patients with severe COPD. Screening and early intervention for depression in patients with severe COPD could improve the HRQL.